ANALISIS PENGARUH KUALITAS AUDIT, DEBT DEFAULT DAN OPINION SHOPPING TERHADAP PENERIMAAN OPINI GOING CONCERN - Praptitorini, Mirna Dyah; Januarti, Indira (Jurnal Akuntansi dan Keuangan Indonesia, 2011)
Responsibilities of auditors currently do not only focus on assessing the fairness of financial statements and detecting fraud, but also assess the company's ability to maintain its survival. This is due to the demands of the shareholders to the auditor to provide early warning about the prospects of a company as consideration before deciding on an investment decision. The research’s goals were to examine the effect of audit quality, debt default, and opinion shopping from going concern opinion. The samples of this research were Manufactures Company that listed in Indonesian Stock Exchange (ISE) from 1997 until 2002. Regression logistic is used in this research for examining the hypothesis. Result of this research, debt default was significant, but the other variables (audit quality and opinion shopping) weren’t significant with going concern opinion.